The Evolution of Emerging Financial Markets"Analysis of The Situation of Algerian Financial Market during The Period (2009/2019)" - بوقرة كريمة (Milev Journal of Research and Studies, 2020)
This research aims to identify the most important concepts related to the emerging financial markets and their position in the economies of the world countries in light of the rapid developments in these markets.This paper focused on studying the situation of the Algerian financial market during the period of 2009 till 2019, which is considered one of the modern markets that is emerged as a result of the economic reforms initiated by Algeria in the early nineties of the last century as a structural imperative to consolidate the economic orientation adopted by the state at that stage.After analyzing the indicators to measure their degree of development, the study concluded that the Algerian Stock Exchange is still far from the efficient emerging market, as it hardly has one indicator that is at the required level. This shows that the Algerian financial market is a traditional market that is far from the aspirations and desired goals in attracting savings to do the opposite process, which is the process of financing the national economy